Die Gattung Orophia Hübner (Lepidoptera: Oecophoridae). - Sattler, Klaus (Contributions to Entomology = Beiträge zur Entomologie, 1968)
Orophia Hübner with type species denisella Denis & Schiffermüller is re-established as a valid genus. Teh five known species have been studied and their male and female genitalia figured and described. Keys based on the male and female genitalia are given. New combinations: Orophia ferrugella (Dennis & Schiffermüller), Orophia mendosella (Zeller) und Orophia zernyi (Szent-Ivany). Nomenclatural ActsOrophia Hübner, 1825 (Oecophoridae), stat. rev.ferrugella (Denis & Schiffermüller, 1775) (Orophia), comb. n. hitherto Tinea ferrugellamendosella (Zeller, 1868) (Orophia), Lectotype; comb. n. hitherto Symmoca mendosellazernyi (Szent-Ivány, 1942) (Orophia), comb. n. hitherto Rhinosia zernyi